Model Network Capability pada UKM olahan hasil laut :studi: Desa Kupang - M Kojim, Achmad Ali Yuddin Hakim (STIE Madani Balikpapan, 2025)
Abstrak Seafood SMEs have an important impact on the economy of coastal areas and areas supplied with seafood resources. Much research has been done on network capability, which addresses the relationships between SMEs and their suppliers, government, and competitors. A view of network capability enables SMEs to change their processes according to market needs and trends, by knowing the relationships between suppliers, customers, and other business partners. Similarly, obtaining information from different sources can stimulate the existing relationship process, which ensures the development of SMEs. This research was conducted with a qualitative approach of descriptive type intended to explain network capability in SMEs in Balonggabus and Balongdowo villages. Information retrieval in this study was taken by means of direct interviews to the village heads of Balonggabus and Balongdowo. If it is not enough, we will explore further by interviewing several members of the Balonggabu and Balongdowo village governments. Most working relationships in kupang processing SMEs are only local and depend on family or personal relationships, there has not been more effort to collaborate with larger external parties such as five-star restaurant companies, industries, and digital markets. Seafood processing SMEs in Balonggabus and Balongdowo villages are still in the early stages of developing network capabilities, and have not yet been able to organize them with a good strategy.